Resources and resource utilization in distance education (2001)
The study on effects of resources and resource utilization in distance education opened with a short history of distance education in Nigeria. The traditional rulers had a way of disseminating information to their subjects through the help of town criers. The federal government of Nigeria gave a legal backing to distance education In 1977. The paper addressed such issues as resources in terms of finance, human, materials and instructional time. The paper ends by exploring the uase of resources in distance education.